Reação do solo e disponibilidade de micronutrientes, em solo de textura média, tratado com lodo de esgoto e cultivado com milho - Jordao Pigozzo, Ana Tereza [UNESP]; Lenzi, Ervim; de Luca Junior, Jorge [UNESP]; Scapim, Carlos Alberto; Vidigal Filho, Pedro Soares; Saraiva da Costa, Antonio Carlos (Universidade Estadual de Maringá (UEM), Pro-reitoria Pesquisa Pos-graduacao, 2008)
The evaluation of micronutrient availability in agricultural soil treated with sewage sludge was developed in Field with maize cultivation on a Dystrophic Red Latosol. The experiment used a randomized complete block design, with the treatments in a split-plot scheme, in time, with six doses of sewage sludge (main-plot treatment) in relation to the five sampling periods for the soil (subplot treatment), with four replications. The sewage sludge was applied in the superficial layer (0-20 cm). The micronutrients Fe, Cu, Mn and Zn were extracted from the soils using a DTPA (diethylenetriaminepentaacetic acid) solution. The same micronutrients were analyzed in the plant tissue after the nitric-perchloric decomposition of the maize samples by spectrometric atomic absorption. The results showed an increasing amount of Fe, Mn, Zn, Cu, Cation Exchange Capacity (CEC) and a decreasing pH in the soil. The increasing doses of sewage sludge increased the Fe, Mn, Cu and Zn availability in the soil solution, and the uptake amount by maize plants were always greater than the control values.
Soil reaction and micronutrient availability of a sandy soil treated with sewage sludge and cultivated with maize
Keywords: sewage sludge; micronutrient availability; maize; tropical soil